The interplay of social and economic capital in coastal community resilience: A scoping review - Firyal Nada Salsabila Agung; Hertria Maharani Putri (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Coastal areas are dynamic and sensitive socio-ecological systems, home to over 40% of the world’s population. Over the past century, they have experienced major socio-economic and environmental changes due to urbanization, industrialization, and ecosystem degradation. Coastal communities, especially those dependent on small-scale fisheries, face multiple challenges from climate change, declining biodiversity, and market pressures. Their ability to cope and adapt depends not only on natural resources but also on social and economic capital. However, the interaction between these two types of capital remains poorly understood, especially in different global contexts. Methods: This study conducted a scoping review of 53 scholarly articles published between 2019 and 2025. Using the three Resilience Capitals framework (C1, C2, C3), the review synthesized evidence on how social and economic capital interact to shape the resilience of coastal communities in both the Global South and Global North. Findings: The synthesis confirms that coastal community resilience is fundamentally a product of a complex, mutually reinforcing interaction where social capital (e.g., trust, networks, collective action) provides the foundation for information exchange and solidarity, while economic capital (e.g., assets, financial capacity) offers the material means for adaptation and recovery. Strong social capital amplifies the utility and reaches of limited economic resources, enhancing adaptive capacity, whereas a deficiency in either capital exacerbates vulnerability. Conclusion: Sustainable coastal development must prioritize the integrated strengthening of both social and economic capital as the foundational core of effective resilience policies. Novelty/Originality of this article: This study offers a comprehensive synthesis of the reciprocal causality between social and economic capitals, providing an evidence-based roadmap for integrated policy interventions, particularly relevant for vulnerable populations in the Global South.